KEDUDUKAN CUCU DARI PIHAK PEREMPUAN DALAM KEWARISAN ISLAM - Agus Anwar Pahutar; Neila Hifzhi Siregar; Hendra Gunawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This paper discusses how the differences between the scholars regarding the position of the grandchildren of women in the acquisition of inheritance in Islam. Because, one of the goals of inheritance is the creation of justice for every heir. However, it is not uncommon for the distribution to happen things that cause the goal of justice not to be achieved. For example, the position of a woman's grandchildren in obtaining inheritance. This is because there is a difference in the understanding of the position of the grandchildren of the woman in obtaining inheritance as zawil arham and a substitute heir.This research is a research library research, using qualitative methods with descriptive analysis, then elaborated by the inductive method. This is done in order to know the opinions of the scholars regarding the position of the grandchildren of women in obtaining inheritance, so that the rationale for patrilineal inheritance and bilateral inheritance is clearly known in Islamic inheritance law.So, based on the research results revealed in this study, it can be described that the position of the grandchildren of the woman in acquiring inheritance is as zawil arham and a substitute heir. So the granddaughter of the woman will inherit as the inheritance received by her mother who died earlier than the heir.